Integration of Community Outreach into the Teaching of Ethics and Legislation in Computing: An Experience Report - Silva, Samira Santos da; Meireles, Sincler Peixoto de (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2026: Anais do VI Simpósio Brasileiro de Educação em ComputaçãoDO - 10.5753/educomp.2026.18851, 2026)
Ethics education is increasingly important in computing due to technology’s societal impact. This paper reports a teaching experience in Ethics and Legislation in Computing at the Federal University of Lavras (UFLA), using a hybrid model combining traditional lectures with active service-learning. Students applied concepts through extension activities at a local school and online via Instagram, and selected topics used a flipped classroom approach. These methods promoted engagement, peer interaction, and autonomous learning. Results indicate that hybrid and service-learning strategies are effective for teaching ethics in computing, enhancing both conceptual understanding and students’ ability to apply ethical principles in real-world scenarios.